Vitamin and fatty acid contents in seeds of some taxa belonging to genus Lathyrus L. growing in Turkey - Sahin, Ahmet; Emre, Irfan; Yilmaz, Okkes; Genc, Hasan; Karatepe, Mustafa (Soc Botanique France, 2009)
In the present study, levels of vitamin and fatty acid composition in mature seeds of some Lathyrus L taxa [L roseus Stev, L tuberosus L, L belinensis Maxted & Goyder, L annuus L, L gorgoni Parl var gorgoni, L cicera L, L sativus L, L stenophyllus Boiss & Heldr, L hirsutus L. L chloranthus Boiss et L aphaca L var affinis (Guss) Arcang] were determined by using HPLC (high-performance liquid chromatography) and VPC (vapour gas chromatography) Palmitic acid (C16 0), stearic acid (C18 0), oleic acid (C18 1 n-9), linoleic acid (Ct8 2 n-6) and alpha-linolenic acid (C18 3 n-3) were found as major fatty acid components in all studied eleven taxa In addition, delta-tocopherol, alpha-tocopherol, alpha-tocopherol acetate and vitamin D3 were found highest level and retinol. retinol acetate, vitamin D2 and vitamin C content (apart from L belinensis and L hirsutus) were found lowest ratio in the examined Lathyrus taxa
Keywords: Lathyrus; fatty acids; vitamins; HPLC; VPC